Compilation of Research Outputs Volume II - BS Psychology 4-1, 2016 4 0 16; 5
THE RELATIONSHIP OF SELF-CONCEPT AND SELF-ESTEEM AMONG THE FRESHMAN STUDENTS OF A LOCAL GOVERNMENT UNIVERSITY--- ABSTRACT: This paper investigates the relationship of self-concept and self-esteem among the freshmen students of a local government university. A total of 170 respondents were chosen to participate in the study, all of whom are undergraduate freshman students of Pamantasan ng Lungsod ng Maynila for A.Y. 2016-2017, whose ages are between 17 and 26. Each student was asked to answer the self-Description Questionnaire III, which was designed by Marsh in 1992 to measure their self-concept. The Rosenberg Self-esteem scale by Rosenberg in 1965, which was developed to measure the self-esteem of individuals was also administered to the respondents. Aside from the relationship of self-concept and self-esteem among freshmen students of PLM, this paper also explores the level of self-concept and self-esteem of the respondents. The results yielded show that there is a significant relationship between the self-concept and self-esteem of the freshman students of PLM.;THE RELATIONSHIP BETWEEN MUSIC PREFERENCE AND PERSONALITY OF SELECTED SCHOOL OF MUSIC DURING THE FIRST TRIMESTER OF A.Y. 2016-2017 ---- ABSTRACT: The present research examined the relationship between music preference and personality as measured by the Short Test of Music Preference Revised (STOMP-R) by Rentfrow and Gosling which focused on the four music dimension (Reflective and Complex, Intense and Rebellious, Upbeat and Conventional, and Energetic and Rhythmic Dimensions) and the Big Five Inventory (BFI) by Costa and Mcrae which focused on the Big Five Personality traits (Extraversion, Agreeableness, Conscientiousness, Neuroticism, and Openness to Experience). The subjects were 75 selected students from the Philippine Women's University-School of Music. The results of the study indicated that there is a significant relationship between music preference dimension and personality traits by correlating using Pearson-r. In addition, a personality development program was proposed in order to help in the personality development of the students in general.;THE IMPACT OF HANDEDNESS ON SPECIFIC INTELLIGENCES AMONG SELECTED COLLEGE STUDENTS---- ABSTRACT: Handedness, overtime , has been considered a basis to determine intelligence due to the brain's inmate lateralization. Upon taking this into consideration, the researchers sought to discover whether handedness posed an impact on the specific intelligence(s) of an individual. Quota sampling was used to gather the 100 right-handed and 100 left-handed third year students from different courses who participated in the study. A correlational research design eas used to examine the association between variables. An intelligence test based on Howard Gardner's Theory of Multiple Intelligence and a short form of the Edinburgh Handedness Inventory - Short Form was utilized to obtain the required data. Descriptive statistics provided a clearer understanding of the observations through organization and summarization, and inferential statistics drew conclusions from a study of the sample conditions that existed within the population. Frequency distribution and mean were utilized to describe the scores gathered from the participants, while Pearson r correlated handedness with the different intelligences. The results yielded a significant negative correlation between handedness and logical-mathematical and visual-spatial intelligence. This reveals a significant inverse relationship handedness and intelligence. It is also found that the dominant intelligence for right-handed individuals is interpersonal, and the dominant intelligence for left-handed individuals is logical-mathematical.;THE RELATIONSHIP BETWEEN COMMUTERS STRESS AND THE MENTAL ABILITY OF SENIOR HIGH SCHOOL STUDENTS IN PLM ---- ABSTRACT: Commuting is labelled as the stress that doesn't pay, according to Psychology Today. The many implications of such stressful travel have been shown to affect not only physical health, but also emotional and psychological state. This study aims to see if a relationship exists between the stress due to commuting and mental ability. The study composed of 240 senior high school students from the Pamantasan ng Lungsod ng Maynila (PLM). The participants were chosen regardless of their age and gender. The research adopted the correlational research design. The researchers developed their own Commuters stress scale (CSS) to measure the participants stress level and adopted the Purdue Non-language Test (PNLT) to assess the respondents mental ability. The research reveals that a significant relationship exists between commuters stress and the mental ability. Kendall tau of (-.94) with a level of significance of 0.05, indicates a weak negative relationship between stress due to commuting and the mental ability of chosen senior high students. The investigation implies that the stress felt during commute is one of the factors that might affect mental ability. Traffic congestions, hunger, humidity and the general feelings of irritability that indistinctly accompany travel cause stress that then affect thinking and academic performance. That is why the detection and management of this stress is essential and need immediate attention before it leads to dire consequences.
The Relationship of Self-Concept and Self Esteem among the freshman Students of a Local Government University.;The Relationship Between Music Preference and Personality of Selected School of Music Students during the first Trimester of A.Y. 2016-2017.;The Impact of Handedness on Specific Intelligences Among Selected College Students.;The Relationship Between Commuters' Stress and the Mental Ability of Senior High School Students in PLM.
Undergraduate Thesis:(B.S.Psychology)- Pamantasan ng Lungsod ng Maynila, 2016.;COLLEGE OF SCIENCE DEPARTMENT OF PSYCHOLOGY.
Keywords: 2 -- 0; 6; 20; 20; 2